Characteristics of exposure to radioactive iodine during a nuclear incident - Zaletel, Katja (Radiology and oncology (Ljubljana), 2024)
Background. During a nuclear accident, numerous products of nuclear fission are released, including isotopes of radioactive iodine. Among them is iodine-131, with a half-life of 8.02 days, which emits ß radiation. For decades, it has been effectively and safely used in medicine. However, in the event of a nuclear accident, uncontrolled exposure can have harmful biological effects. The main sources of internal contamination with iodine-131 are contaminated air, food and water. The most exposed organ is the thyroid gland, where radioactive iodine accumulates via the Na+/I- symporter (NIS). NIS does not distinguish between radioactive iodine isotopes and the stable isotope iodine-127, which is essential for the synthesis of thyroid hormones. Exposure to radioactive iodine during a nuclear accident is primarily associated with papillary thyroid cancer, whose incidence begins to increase a few years after exposure. Children and adolescents are at the highest risk, and the risk is particularly significant for individuals living in iodinedeficient areas. Conclusions. Ensuring an adequate iodine supply is therefore crucial for lowering the risk of the harmful effects of exposure to radioactive iodine at the population level. Protecting the thyroid with potassium iodide tablets significantly reduces radiation exposure, as stable iodine prevents the entry of radioactive iodine into the thyroid. Such protection is effective only within a narrow time window - a few hours before and after the exposure and is recommended only for those under 40 years of age, as the risks of excessive iodine intake outweigh the potential benefits in older individuals
Keywords: jedrska nesreča; kalijev jodid; radioaktivni jod; rak ščitnice; ščitnica